My best friend's wedding - Hogan, J. P.; Zucker, Jerry; Bass, Ronald; Roberts, Julia 1967-.; Mulroney, Dermot; Diaz, Cameron; Everett, Rupert; Tri-Star Pictures; Columbia TriStar Home Video (Firm). ([Culver City, Calif.] Columbia TriStar Home Video, 1997)
Commitment-shy Jules Potter has four days to steal back her best friend Michael before he marries someone else.
Originally produced as motion picture in 1997.
"Magnavision Inc. distributor in the Philippines"--Container.
Editors, Garth Craven, Lisa Fruchtman ; music, James Newton Howard.
Julia Roberts, Dermont Mulroney, Cameron Diaz, Rupert Everett.
VHS ; hi-fi, Dolby surround.
Donated by Prof. Amor Olaguer-Aljibe.
Keywords: Weddings in motion pictures; Romantic comedy films; Feature films